HOW CAN BUSINESS PROCESS MANAGEMENT SUPPORT THE DEVELOPMENT OF OMNI- CHANNEL SERVICES? - Juliatto, Dante Luiz (Anais New Science Publishers | Editora Impacto, 2024)
Purpose - This paper investigated how Business Process Management (BPM) contributes to the development of omni-channel services.Design/methodology/approach - For that, multiple case studies were carried out in different a contact center of the Brazilian Ministry of Education.Findings - Results suggest that BPM may be an effective approach to structure processes before they move towards omni-channel implementations, especially in service organizations where process tangibility is an issue.Originality value - We bridged two research streams (i.e., BPM and omnichannel services) that have been traditionally conducted in isolation. Although much has been studied in both topics, investigating their combination might lead to new insights to the body of knowledge that may have been neglected over the years.